Frequency, clinical and angiographic characteristics, and outcomes of high-risk non-ST-segment elevation acute coronary syndromes patients with left circumflex culprit lesions. (15th January 2016) - Halim, Sharif A.; Clare, Robert M.; Newby, L. Kristin; Lokhnygina, Yuliya; Schweiger, Marc J.; Hof, Arnoud W.; Hochman, Judith S.; James, Stefan K.; White, Harvey D.; Widimsky, Petr; Betriu, Amadeo; Bode, Christoph; et al.
Abstract: Background: The relationship between culprit vessel, infarct size, and outcomes in non-ST-segment elevation acute coronary syndromes (NSTE ACS) is unclear. In some reports, the left circumflex artery (LCX) was more often the culprit at angiography than the right coronary artery (RCA) or left anterior descending artery (LAD), and infarcts were larger with LCX culprits. Methods: We determined culprit vessel frequency and initial patency (TIMI flow grade), median fold elevation of peak troponin above the upper limit of normal, and outcomes (30-day death or myocardial infarction [MI] and 1-year mortality) by culprit vessel in high-risk NSTE ACS patients in the EARLY ACS trial. Results: Of 9406 patients, 2066 (22.0%) had angiographic core laboratory data. We evaluated 1774 patients for whom the culprit artery was not the left main, a bypass graft, or branch vessel. The culprit was the LCX in 560 (31.6%), LAD in 653 (36.8%), and RCA in 561 (31.6%) patients. There were fewer women (24.1%) and more prior MI (25.5%) among patients with a culprit LCX compared with those with a culprit LAD or RCA. Patients with LCX (21.2%) and RCA (27.5%) culprits more often had an occluded artery (TIMI 0/1) than did those with LAD (11.3%). Peak troponin elevation was significantly higher for LCX than RCA or LAD culprits. LCX culprit vessels were not associated with worse 30-day or 1-year outcomes in adjusted models. Conclusions: Among patients with NSTE ACS, the frequencies of LCX, LAD, and RCA culprits were similar. Although LCX lesions were associated with higher peak troponin levels, there was no difference in short- or intermediate-term outcomes by culprit artery.